Investigação do envolvimento do receptor TRPA1 em diferentes modelos de depressão em camundongos - Pereira, Gabriele Cheiran (2024)
Major depressive disorder (MDD) is a psychiatric mood disorder with heterogeneous characteristics that affects one in five individuals over the course of their lives. Currently, it is estimated that approximately 280 million people worldwide have MDD, which has already been highlighted as the third leading cause of disability worldwide. Despite this widespread incidence, its pathophysiological mechanisms have not yet been fully elucidated. This, combined with the high rates of refractoriness to currently available pharmacological and non-pharmacological treatments, highlights the importance of clarifying its pathophysiology, as well as investigating new targets and substances with therapeutic potential. Transient receptor potential ankyrin 1 (TRPA1) consists of a nonselective transmembrane cation channel that acts as a sensor for oxidative species and inflammatory mediators. This receptor is expressed in several tissues, including the central nervous system (CNS), and its involvement has already been suggested in models of inflammatory pain, multiple sclerosis and migraine. However, little is known about the involvement of this channel in psychiatric disorders, such as MDD. Thus, the general objective of this work was to evaluate the involvement of TRPA1 in different experimental models of MDD in mice. First, in order to provide an overview of the participation of the transient receptor potential (TRP) family in MDD, a narrative review article was developed (manuscript 1). Then, through the chronic corticosterone administration (CCA) model, the participation of TRPA1 was investigated, as well as behavioral and oxidative parameters evaluated after this protocol (article 1). Next, the standardization of a new experimental model of MDD was performed, combining two different types of stressors: environmental stress (social isolation - SI) and low-grade inflammatory stress (weekly administration of lipopolysaccharide, LPS) (manuscript 2). In the narrative review, after applying the inclusion and exclusion criteria, 17 studies were described that investigated the involvement of different TRPs in different animal models of MDD. In article 1, the participation of TRPA1 was suggested in the behavioral impairment and oxidative imbalance induced by ACC, where a reduction in the immunocontent of this receptor in the hippocampus and a tendency for increase in the prefrontal cortex were also observed. In addition, the administration of the antagonists HC-030031 and A-967079 reversed both the behavioral changes and the increase in the levels of hydrogen peroxide (H2O2), an important TRPA1 agonist. Finally, in manuscript 2, it was demonstrated that the association of IS with LPS exposure induced changes in different behavioral spectra related to MDD, including depressive-like and anxiety-like behaviors, as well as cognitive impairment. In addition, after the IS protocol, an increase in TRPA1 gene expression was observed in the hippocampus. Thus, it can be concluded that the TRPA1 receptor participates in the pathophysiological mechanisms of different preclinical models of MDD.